Estudio de factibilidad para la creación de una empresa productora de yogurt de arazá y su comercialización en la provincia de Sucumbíos - Zúñiga Figueroa, Adriana Karina (2014)
Dairy products and especially the higher value added such as yogurt achieve acceptance in the market. That is why the creation of a producer of yogurt arazá, which will have appropriate processes to ensure excellent product quality to reach the quality standards set by the industry seeks. The main objective was raised for this thesis was to conduct a feasibility study for the creation of a producer of yogurt arazá and marketing in Sucumbios province, in order to contribute to social, economic and business development, province of Sucumbios. This work primarily contains bibliographic backups for the practical development of the various studies of the thesis. Also materials and methods, the same that served that facilitated the process and presentation of results involved in the different studies are presented. The methods used inductive, deductive, analytical and descriptive method is; techniques applied were observation and survey. For market research surveys were administered to 381 families in the province of Sucumbios Product as potential applicants and 278 surveys of vendors such as supermarkets, grocery stores in the province of Sucumbios, establishing that for the first year has a potential demand for 51,934 families; a real demand for 47,779 families and an effective demand for 2'722.441 in liters of yogurt, considering that there is market demand unmet 2'588.286 liters of yogurt. The technical study the macro and micro localization company DELIYUR CIA was raised. LTDA., And determined that the micro location will be in the province of Sucumbios in Lago Agrio, in the streets Cofanes and Av. Nueva Loja. due to the availability of means and resources, especially access to the raw material. The company will have one manager, one legal adviser, accountant 1 secretary, 1 Head of production, one worker and one driver vendor partners that will help the development of the company and meet the demands of consumers. The unmet demand shows the great opportunity for the company to product placement in the market and depending on the results the company is able to offer 37,200 liters of yogurt arazá representing capacity utilization at 80% capacity Total to offer the best quality product at affordable prices. In engineering project, the distribution of the plant is determined, the process flow, circuit diagram and technical (equipment, machinery) requirements, as well as furniture and fixtures, which are required for normal was designed perform their duties within the company. In the organizational and administrative study the organizational structure of the company is described statutory and regulatory factors needed for proper implementation of the company in the country are considered, the philosophy of the company decided it was established that the company will be a Limited company, in addition to the organic structure it is implemented - for functional management levels, executive, legislative, advisory, and operational assistant, also a proposed manual functions as a basis to implement is the organization of the company. The economic study comprised all investments in fixed assets, deferred assets, working capital, financing, and all financial statements that are required to ensure the financial assessment and identify whether the project is feasible or not; obtaining the required investment is $ 38,544.96 which is $ 23,544.96 equity and a credit to the bank $ 15,000.00 Building 4-year term. The financial evaluation produced the following results: NPV, gives a value of $ 5.831,34que feasible for implementation. The IRR is 2.45%, which is equally satisfactory value for the project. The benefit - cost (RB / C) is $ 1.15, which means that for every dollar invested will have a recovery of $ 0.15 cents. The capital recovery period (PRC) is 4 years, 7 months and 15 days, sensitivity values are 0.99 with rising costs and 0.99 with lower costs. Changes in costs and revenues, increased by 4.85% and decreased in 4.22%, which allows to show that the project is not sensitive to these changes. Establishing that the investment is profitable for the company, because the percentage of income that has been considered is 15%, placing the product on the market for $ 2, 87 The competitive advantage that will differentiate DELIYUR CIA. LTDA. be product quality and price, because the best raw materials for the manufacture of the product is used, without implying too high a price increase. The product price is very competitive compared with other products in the same features offered on the market.